A simplified method for modeling the thermal performance of storage tanks containing PCMs. (25th February 2016) - Belmonte, J.F.; Eguía, P.; Molina, A.E.; Almendros-Ibáñez, J.A.; Salgado, R.
Highlights: A simple method for modeling the performance of a TES system with a PCM is presented. The method is generally applicable to any TES system containing a PCM. The method is particularly suitable for application during early design stages. Only the most relevant input parameters (a total of 10) are required by the method. The method can be implemented in whole-building simulation tools such as TRNSYS. Abstract: This work presents a simple method for modeling the performance of a thermal energy storage (TES) system that contains a phase-change material (PCM). The developed approach is similar in concept to the bypass factor method, widely used in air conditioning applications to estimate the outlet air conditions from a coil. The proposed method provides reasonably accurate results while requiring only the most relevant input parameters (a total of 10) commonly available during the early stages of TES system design, wherein the impact of decision making is greatest and not all aspects of the TES system may be fully defined. The method is particularly suitable for application during preliminary stages. The results exhibit a good agreement (maximum discrepancies in the cumulative energy of below 13%), with the experimental results consisting of a total of 21 charging and discharging cycles of two TES systems. Each system has a different heat exchanger and contains a different PCM: one system contains an inorganic material, and the other contains an organic material. The method is generally applicable to any TES system with a PCM, thereby simplifying the performance characterization and implementation of such TES systems in energy analysis tools such as TRNSYS ® .